Non-metallic iodine single-atom catalysts with optimized electronic structures for efficient Fenton-like reactions - Junjun Pei; Jianbin Liu; Kaixing Fu; Yukui Fu; Kai Yin; Shenglian Luo; Deyou Yu; Mingyang Xing; Jinming Luo (Nature Communications)
Abstract In this study, we introduce a highly effective non-metallic iodine single-atom catalyst (SAC), referred to as I-NC, which is strategically confined within a nitrogen-doped carbon (NC) scaffold. This configuration features a distinctive C-I coordination that optimizes the electronic structure of the nitrogen-adjacent carbon sites. As a result, this arrangement enhances electron transfer from peroxymonosulfate (PMS) to the active sites, particularly the electron-deficient carbon. This electron transfer is followed by a deprotonation process that generates the peroxymonosulfate radical (SO5 •−). Subsequently, the SO5 •− radical undergoes a disproportionation reaction, leading to the production of singlet oxygen (1O2). Furthermore, the energy barrier for the rate-limiting step of SO5 •− generation in I-NC is significantly lower at 1.45 eV, compared to 1.65 eV in the NC scaffold. This reduction in energy barrier effectively overcomes kinetic obstacles, thereby facilitating an enhanced generation of 1O2. Consequently, the I-NC catalyst exhibits remarkable catalytic efficiency and unmatched reactivity for PMS activation. This leads to a significantly accelerated degradation of pollutants, evidenced by a relatively high observed kinetic rate constant (k obs ~ 0.436 min− 1) compared to other metallic SACs. This study offers valuable insights into the rational design of effective non-metallic SACs, showcasing their promising potential for Fenton-like reactions in water treatment applications.